Socio-Economic Conditions and Occupational Health Hazards of Fish Hook Makers in Rural Bengal: Life Sciences-Zoology for Novel drug discovery - Animesh Mandal; Rajendra Prasad Mondal (International Journal of Life Science and Pharma Research, 2022)
Fish hook making is subject to health risks In the rural areas of West Bengal, a notable part of population is engaged in fish related activities in diverse ways either instantaneously or incidentally. The sector of activity of fish hook making is essentially rural and it being most haphazard, no focus has been given to the occupational health problems of these workers by politicians, planners, administrators and scientists. The objectives of our study is to access the occupational health hazards of fish hook makers and to give essential suggestions for the mitigation measures of those hazards resulting in a more desirable quality of life for the countryside inhabitants. A standardized structured questionnaire, with modification to suit the local context was used to collect the data. Data was analyzed in the form of percentage (%),mean and standard deviation. Out of the total 51 respondents 15 weremale and 36 were female. It revealed that in supreme number of cases hook workers experience hazards due tomachinery induced injury, musculo-skeletal disease, eye disease, skin disease due to working in unhealthy workplaces, manual handling of machines and not using personal protective equipments. So, fish hook makers need a notable degree of consciousness through regular safety training for minimizing their occupational health hazards.,